MEASURING THE URGENCY FOR THE ESTABLISHMENT OF A NATIONAL GOVERNMENT LEGISLATION INSTITUTION IN THE PURSUIT OF STRUCTURING LAWS AND REGULATIONS IN INDONESIA - Santos, Jaka; Vijay, Muhammad (Transnational Business Law Journal, 2022)
The absence of a special agency that centrally and specifically regulates and manages government affairs within the area of establishing laws and regulations, just as the legislative body of the House of Representatives (“DPR”) is the main focus of the author to conduct a research. Through the writing of conceptual critical ideas with a normative juridical approach, it is discovered that there are several opportunities for the establishment of a government national legislative body. First, it is by the adoption of the omnibus law in the establishment of laws and regulations through Law Number 11 of 2020 on Job Creation. Second, the government is not yet has a specific institution that centrally and specifically regulates and manages government affairs within the area of establishing laws and regulations just as the legislative body of DPR. In fact, there is an urgency to establish a national government legislative body. First, as long as the establishment of laws and regulations remained spread throughout the Ministries/Institutions, and the coordination function or harmonization is performed at the Ministry of Law and Human Rights and the State Secretariat/Cabinet Secretariat, the process is not as simple as if it is in one solid institution integrated mastery of design materials whose substance is in across sectors. Second, it is the mandate of Law Number 15 of 2019 on Amendments to Law Number 12 of 2011 on the Establishment of Legislation. Third, it is the post Constitutional Court Decision Number 91/PUU-XVIII/2020 with respect to Law Number 11 of 2020 on Job Creation. In order to revise the Job Creation Law in conformity with the two-year deadline, the government could immediately establish a National Legislative Institution to be in charge of organizing, synchronizing, and tidying up all laws and regulations from the central to the regions levels. Fourth, it is the post decisions of the Constitutional Court Number 137/PUU-XIII/2015 and Number 56/PUU-XIV/2016 as the central government is no longer authorized to revoke Regional Regulations, indicates the importance of building synergy between the central government and regional governments in managing laws and regulations at the provincial level and districts/cities.